Upaya Meningkatkan Kecerdasan Naturalis melalui Perilaku Peduli Lingkungan pada Siswa Sekolah Dasar: Analisis Review - fransiska rahmawati; Irvania Emiliawati; Ita Tri Astuti; Siti Fatimah; Conny Dian Sumadi (Universitas Negeri Surabaya, 2022)
ABSTRACT This study aims to determine efforts to increase naturalist intelligence through environmental care behavior in elementary school students. Researchers used the google schoolar database to obtain reference articles that were used as literature reviews. Efforts to increase naturalist intelligence through environmental love behavior in elementary school students based on the results of the review are still encouraging and self-awareness from students. Naturalist intelligence needs to be improved so that it is ready and concerned about the environment to be able to be implemented. Naturalist intelligence is important for elementary school students to have because nowadays a lot of natural damage is caused by human hands. Elementary school students have an important role in carrying out the mission of caring for the environment. The learning process for elementary school students is still in the stage of recognizing, caring for, and protecting the environment and animals and plants that exist in nature. Humans and the environment do each other's daily activities. Instilling the character of students to be able to care about the environment which is driven by encouragement from parents, teachers, and self-awareness. This concern for the environment can be integrated in learning science and environmental education for elementary students. ABSTRAK Penelitian ini bertujuan untuk mengetahui upaya meningkatkan kecerdasan naturalis melalui perilaku peduli lingkungan pada siswa sekolah dasar. Peneliti menggunakan database google schoolar untuk mendapatkan referensi artikel yang digunakan sebagai literature review. Upaya peningkatan kecerdasan naturalis melalui perilaku cinta lingkungan pada siswa SD berdasarkan hasil review masih membutuhkan dorongan dan kesadaran dari diri siswa. Kecerdasan naturalis perlu untuk ditingkatkan agar kepekaan dan kepedulian terhadap lingkungan mampu untuk diimplementasikan. Kecerdasan naturalis penting untuk dimiliki oleh siswa SD karena saat ini banyak kerusakan alam yang disebabkan oleh tangan manusia. Siswa SD mempunyai peranan yang penting dalam mengemban misi tentang kepedulian terhadap lingkungan. Proses pembelajaran siswa SD masih dalam tahapan untuk mengenal, merawat, dan menjaga lingkungan serta hewan dan tumbuhan yang ada di alam. Manusia dan lingkungan saling berkesinambungan pada kegiatan sehari-hari. Penanaman karakter siswa untuk dapat peduli terhadap lingkungan dibutuhkan dorongan dari orang tua, guru, dan kesadaran pada dirinya. Kepedulian terhadap lingkungan ini dapat diintegrasikan dalam pembelajaran tematik pada siswa SD.